OTDR Integrated in OLT PON Port - Yuehua Ou; Yan Ren (Dianxin kexue)
Along with the propulsion of the“broadband China”strategy,FTTx has been deployed massively,therefore there are more and more requirements on detecting optic fiber faults, solutions with low cost are needed to detect fiber faults and improve the efficiency of PON operation and maintenance. OTDR integrated in OLT PON port was studied, and the implementation and the cost of different wavelength solutions were analyzed and compared. The PON system architecture based on OTDR integrated in PON port was proposed, and the requirements of OTDR detection ability and the limitation requirements of OTDR effecting the physical parameters of PON port and the communication service were given. The goal is that OTDR integrated in PON port can satisfy the requirements of operators' PON detection, and improve the efficiency of PON operation and maintenance.